Dimensional evolution of graphene-based nanomaterials for sensor and supercapacitor applications - Foo, Chuan Yi (2018)
The versatility of graphene and its derivatives from inventive synthesis method have evolved throughout the years, which provided avenues that precisely tune their structure and functionality for specific applications. Nevertheless, there are only several graphene-based products that have been successfully commercialized into the market. The main reason behind this is the lack of concrete performance metrics of graphene and its derivatives demonstrating their true value proposition in other segments. In this thesis, the investigation and justification of the evolution process of graphene derivatives were discussed in terms of graphene in different dimensions, which ultimately provide significant insights into diverse industrial applications. In the first evolution stage, graphene with its natural 2D nanosheet structure was being employed as an “electronic blanket” in photoelectrochemical (PEC) sensing platform. The existence of 2D graphene (rGO) blanket in cadmium sulfide (CdS) modified carbon cloth (CC) electrode increased the photocurrent intensity by two orders of magnitude, compared to that of without graphene. 2D graphene blanket can also provide intimate integration between the nanoparticles and current collector substrate, thus contributing to a sensitive copper ion detector with a linear detection range of 0.1 to 40.0 μM and a detection limit of 0.05 μM. In the second evolution stage, graphene was modified with nickel cobaltite (NCO) to produce a hierarchical 3D rGO/NCO nanostructure. Upon modification, the morphology of the graphene evolved from nanosheet into a petal-like nanostructure. This petal-like rGO/NCO nanostructure exhibits excellent supercapacitive performance (282.95 F g-1), which is 1.5 times higher than that of pure NCO. Besides, intimate integration of NCO on the rGO nanosheet resulted in an efficient contact between the electrode/electrolyte interface, thus contributing to superior capacitance retention, which is 46% better than that of pure NCO. In the third evolution stage, graphene was self-assembled and reinforced with polypyrrole (Ppy) into a free-standing 3D aerogel matrix. The self-agglomeration and oxidative polymerization of rGO and Ppy occurred synergistically in a controlled water bath environment, which resulted in an elastic and conductive compression sensor. The presence of flexible rGO nanosheets as an aerogel backbone provided a strong mechanical support which could be compressed more than 50% and recovered to its original structure in less than 5 seconds with minor mechanical deformations. Lastly, in the final stage of evolution, graphene modified polylactic acid (PLA) was employed to develop a 3D printed electrode (3DE) using a commercial 3D printer. Graphene provided additional electrical conductivity properties to the insulating PLA matrix, which then proficiently fabricated into a supercapacitor and PEC sensor. They had a photocurrent response that exceeded expectations (~724.1 μA) and a lower detection limit (0.05 μM) than an ITO/FTO glass electrode. In conclusion, the neoteric findings in this research provide a significant leap in functional graphene nanomaterial fabrications. Even though graphene has been extensively employed in laboratory research, the evolution and modification of graphene nanomaterials can eventually reveal its true potential in other industrial applications.